A Comparative Perspective on Constitutional Complaint: Discussing Models, Procedures, and Decisions - M. Lutfi Chakim (Constitutional Review, 2019)
The constitutional complaint is one of the important constitutional court jurisdictions that can be described as a complaint or lawsuit filed by any person who deems his or her rights has been violating by act or omission of public authority. Currently, the constitutional court in many countries have adopted a constitutional complaint system in a variety of models. However, the first application of the constitutional complaint jurisdiction came from Europe. In Austria, the constitutional complaint is allowed against the administrative actions but not against the court decisions. While Germany and Spain have a similar model that is a complaint against an act of the public authority including court decisions. In Asia, it is imperative that the court in Asia actively participate in the Association of Asian Constitutional Courts and Equivalent Institutions (AACC). The AACC members have adopted a system of constitutional adjudication in a variety of models, and when it comes to jurisdictions, out of sixteen AACC members, there are four countries (Azerbaijan, South Korea, Thailand, and Turkey) have the constitutional complaint in their jurisdictions. In Azerbaijan, constitutional complaint is comparatively broad. Azerbaijan’s Constitutional Court can handle constitutional complaint against the normative legal act of the legislative and executive, an act of a municipality and the decisions of courts. In contrast, even though constitutional complaint in South Korea and Thailand can be against the exercise and non-exercise of state power, constitutional complaint cannot be filed against court decisions. In Turkey, the constitutional complaint mechanism is coupled with the regional system of human rights protection. The Turkish Constitutional Court handles complaints from individuals concerning violations of human rights and freedoms falling under the joint protection of the Turkish Constitution and the European Convention on Human Rights (ECHR). This paper argues that constitutional complaint represents the main part of the constitutional court, and through a comparative perspective among three countries in Europe and four AACC members are expected to provide lessons for the other AACC members that do not have a constitutional complaint mechanism, such as Indonesia.